Instagram and Bookflix: A promotion strategy to develop the SMAN 20 Bandung Library - Raysa Atripa Royyan; Salwa Ghaida Rakhmawati; Yezika Rachman (Universitas Pendidikan Indonesia, 2025)
With the society's lifestyle significantly influenced by information and communication technology, especially social media, students tend to spend more time in front of the screen than reading books and looking for the information they need by visiting the library. Even so, school libraries can effectively use technology such as social media to carry out engaging and interactive activities to encourage students' interest in reading. This program is part of implementing a student internship program using the action research stage. The aim is to discover how Instagram and Bookflix, as promotional media, can increase student interest in visiting and build a successful promotional strategy for the SMAN 20 Bandung library. The method used is action research. The results show that the library promotion used at SMAN 20 Bandung uses Instagram social media and the school bulletin board